Someone I used to know [large type] - Toon, Paige, 1975- (Thorndike Press, a part of Gale, a Cengage Company, 2024)
"Then: At sixteen, George is the foster brother Leah never asked for. Beautiful and troubled, he struggles to come to terms with his circumstances even as Leah is drawn ever closer to him. Theo's wealthy family have mysteriously pulled him out of boarding school and he's now enrolled with Leah and George. When their worlds collide that summer, George, Leah and Theo form a bond they believe will be unbreakable. But life doesn't always go to plan... Now: Shocking news brings Leah back to Yorkshire, baby daughter in tow. But Emilie's father Theo isn't with them, and George has unexpectedly returned. After half a lifetime, have they healed the scars of their pasts? Will coming back home set their hearts in a different direction?"--Amazon.